Robust-fragile watermarking using integer wavelet transform for tampered detection and copyright protection - Budi, Hendra; Ernawan, Ferda; Amrullah, Agit (College of Education, Al-Iraqia University, 2024)
The use of the internet and advanced technologies enables the distribution of information and data through diverse digital images. Nevertheless, this ease of use comes with the potential risk of data misappropriation, encompassing unauthorized alterations, duplications, and reproductions of digital images. Ongoing research is being conducted in the field of watermarking to enhance the capabilities of protecting digital images. The objective of this work is to enhance the strength of copyright protection and the vulnerability of watermarking for authentication in digital images by utilizing the Integer Wavelet Transform (IWT). The watermarking approach involves embedding a durable watermark in the red layer and a delicate watermark in the blue layer of the host image. The watermark is incorporated into the singular value of the Singular Value Decomposition (SVD). The red layers with watermarks are generated using a Hash function and subsequently integrated into the blue layer using the Least Significant Bit (LSB) method. The experimental findings demonstrate that the proposed strategy effectively enhances both imperceptibility and robustness in comparison to the previous benchmark research. The suggested scheme attained an average PSNR value of 51,935 and an average SSIM value of 0.976. The proposed scheme demonstrated an average improvement of 14.19% in PSNR compared to existing schemes. This study offers efficient and suitable remedies for safeguarding digital images against unauthorised and alteration without consent.